Pre-marital education (PME) program for marriage readiness and stunting prevention to women of childbearing age - Leila Nisya Ayuanda; Nur Intan Kusuma; Amin Aji Budiman (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Indonesia is one of the countries with a high burden of malnutrition, including stunting. One preventive measure for stunting is the optimization of pre-pregnancy services (preconception). Preconception services, especially for prospective brides and grooms, aim to identify and modify biomedical, psychological, and social risks related to women's health and pregnancy conditions through an optimal early detection strategy. Current issues regarding stunting can indeed be prevented through optimal pregnancy and marriage planning. Therefore, a strategy is needed to develop comprehensive pre-marriage planning through premarital classes.Purpose: To determine the effectiveness of pre-marital education (PME) program for marriage readiness and stunting prevention to women of childbearing ageMethod: This research used a quantitative research design with a quasi-experimental one-group pretest-posttest approach. The instrument used a questionnaire on the physical, psychological, and social readiness of premarital individuals that had been tested for validity and reliability. The sampling method used accidental sampling, and 49 prospective brides and grooms were obtained as participants.Results: The results indicated that the